Case Report: Lenvatinib for the treatment of recurrent hepatocellular carcinoma in people living with HIV: a report of two cases - Morsica, Giulia; Bertoni, Costanza; Hasson, Hamid; Messina, Emanuela; Uberti Foppa, Caterina (Frontiers in Oncology, 2023)
The use and choice of the best systemic treatment is gaining increasing interest in people living with HIV (PLWH) because hepatocellular carcinoma (HCC) represents an increasing cause of morbidity and mortality in this setting and most HCCs are diagnosed in the advanced stage. Ten years ago, the multi-kinase inhibitor lenvatinib was approved in the first-line setting. However, to date, no data on the efficacy and tolerability of lenvatinib in PLWH from clinical trials and real-life studies are available. Case 1 was a gentleman with hepatitis B virus–related cirrhosis who underwent orthotopic liver transplantation for HCC and developed peritoneal metastasis several years later. Lenvatinib treatment was selected at HCC recurrence. This participant maintained undetectable HIV viremia and a relatively preserved immune status during 6 months of systemic treatment with lenvatinib. After 6 months, he discontinued lenvatinib for progression of the disease (growing of peritoneal metastasis) and uncontrolled hypertension. Case 2 was a gentleman with hepatitis C–genotype 1a–related cirrhosis who experienced unresectable recurrences after radiofrequency thermal ablation of the tumor. At the first recurrence, HCC was treated with six cycles of trans-catheter arterial chemoembolization; at the second recurrence, the participant underwent trans-catheter arterial radioembolization; and at the third recurrence, he received lenvatinib. A week after the start of lenvatinib, the participant had liver decompensation and discontinued therapy. The presently reported cases showed low tolerability of systemic therapy with lenvatinib in PLWH. Cumulative data are necessary to define the position of lenvatinib in this setting.